Exploring spatial distribution characteristics of Populus simonii Carr coarse roots using ground penetrating radar - Van Cuong, Le; Dai, Yunze; Manh, Vu; Van Hop, Nguyen; Van Quy, Nguyen (Journal of Forestry Science and Technology, 2024)
A comprehensive root database holds paramount importance for agro-forestry endeavours, providing valuable insights into the ecological characteristics and stability of plant species. However, the creation of such databases presents a formidable challenge. This study is devoted to shedding light on the spatial distribution characteristics of coarse roots (diameter ≥1 cm) in Populus simonii trees, which naturally flourish in Tongde County, Thanh Hai province, China. Ground-penetrating radar (GPR) technology was employed to investigate the distribution of these coarse roots, while tree root diameters were estimated through controlled experiments involving buried objects. A total of 40 P. simonii trees were meticulously selected for data collection, and the coarse roots of these trees were categorized into three diameter classes: 1-2 cm, 2-3 cm, and ≥3 cm. The study findings have unveiled a robust correlation between the density of coarse roots and the diameter at breast height (dbh) of the trees. Moreover, the total coarse root density moderately correlates with canopy width and tree height within a horizontal plane extending 3-5 m from the tree base and a vertical plane at a soil depth of 20-40 cm. This study underscores the effectiveness of GPR in elucidating the spatial distribution of tree roots and accurately estimating root diameters. This underscores the potential of GPR to significantly enhance investigations related to root ecology and below-ground biomass estimation.